COMPARATIVE ANALYSIS OF QUALITY CONTROL MEASURES IN CLINICAL LABORATORIES: ASSESSING THE IMPACT ON DIAGNOSTIC ACCURACY AND PATIENT SAFETY - Ahmed Halosh Alinazi, Faiz Azbi Almutairi, Hmdi Ali Alinazi, Abdulmajed Habis Alinazi, Omar Jafal Alinazi, Abdulkareem Mohmmed Alshamri (Chelonian Research Foundation, 2022)
Quality control measures are essential for ensuring the accuracy and reliability of clinical laboratory results, which directly impact patient care and safety. This study aims to conduct a comparative analysis of various quality control measures implemented in clinical laboratories in Saudi Arabia and assess their impact on diagnostic accuracy and patient safety. The research will focus on the contributions of the authors, who are laboratory technicians, in implementing and evaluating these quality control measures. The study will employ a mixed-methods approach, combining quantitative data analysis of quality control metrics and qualitative data from interviews with laboratory personnel. The findings of this study will provide valuable insights into the effectiveness of different quality control measures in the context of Saudi Arabian clinical laboratories and their potential impact on improving diagnostic accuracy and patient safety.